Advancing Social Justice Through Conflict Resolution Amid Rapid Urban Transformation of the San Francisco Bay Area - Reinke, Amanda Jo (2016)
Since the 1970s, communities throughout the United States have been enthusiastically adopting dispute resolution mechanisms outside the formal legal system. Emerging from the reparative turn in sociolegal studies and widespread social critique in the 1960s and 70s, alternative justice models have been theorized, developed, and implemented by scholars and affected communities. In particular, alternative justice – forms of conflict resolution outside the formal legal system – seek to subvert the formal legal system’s disproportionate impact on marginalized communities by providing accessible, non-criminalizing, and inclusive conflict resolution. Advocates claim such models advance social justice by uplifting restoration rather than retribution, emphasizing democratic processes, and utilizing conflict resolution as a platform for individual and community empowerment and capacity building. Fourteen months of ethnographic research with alternative justice practitioners and their clients reveals discrepancies between alternative justice theory and practice. In particular, complex political, economic, and social constraints embedded within a rapidly transforming urban environment make achieving broader impacts (e.g. empowerment, capacity-building) and allying with related social justice mechanisms particularly challenging at both the individual practitioner and organizational levels. Situated at the intersection of anthropology, sociology, and legal studies, this dissertation contributes to theoretical understandings of informal justice theory and practice. By examining the ways informal justice is intricately interwoven into the fabric of everyday and state violence, the complex relationship between alternative justice practice and contemporary social justice efforts, and the ways in which the mythico-history of alternative justice influences practice, findings presented herein can inform both theoretical and practical approaches to contemporary alternative justice